Akuntabilitas Pengelolaan Bantuan Operasional Sekolah (Bos) Di SMA Negeri 1 Siompu Barat - Ibnu Haldun; Zainul Abidin; Asmiddin Asmiddin (UNIVED PRESS, Universitas Dehasen Bengkulu, 2026)
This study aims to explain the accountability of BOS fund management at SMA 1 Siompu Barat. This study uses a descriptive method with a qualitative approach. The data sources are primary and secondary data. Data were collected using interviews, observation, and documentation techniques. Data analysis techniques were carried out by preparing and organizing data, reducing data, and presenting data. The results of the study show that accountability tends to be oriented towards the fulfillment of financial reports and does not yet ensure the achievement of learning programs, so that many curricular and extracurricular programs are not running. Accountability must be expanded in scope from finance to performance.